Infraspecific Delimitation of Acacia senegal (Fabaceae) in Uganda - Kakudidi, Esezah; Mulumba, John Wasswa (Scientific Research, 2011)
The wide variation in Acacia senegal has presented taxonomic uncertainties and unresolved contradictions in previous studies. In this study numerical taxonomic principles and multivariate analysis (UPGMA PCoA and PCA) were used basing on 69 characters derived from growth form, branchlets, leaves, flowers, pods and seed. Three taxa, namely; variety senegal, leiorhachis and kerensis have been discerned and described significantly improving the delimitations of previous studies. The wide variation within var. senegal has been split into three recognizable variants and that of var. leiorhachis into two. The most important characters for differentiating the taxa include leaf breadth and length, pinna length and its ratio to pinna breadth, number of leaflet pairs, petiolar gland shape, petiolar and rachis gland size, stem and branch bark texture, stem and branchlet colour, under-bark colour for stem and branches, pod apical shape, growth form, crown shape, and prickly state of leaves. An identification key has been constructed which, for the first time, can be used to assign herbarium specimens to their respective taxa.
Keywords: Acacia Senegal; Infraspecific; Multivariate Analysis; Numerical Taxonomy; Uganda